Study on Juvenile Growth Performance of Non-Descript Country Chicken Under Intensive System of Management in Puducherry - Binuni Rebez E; Hemavathi A; Venugopal S (The Indian Veterinary Journal, 2024)
A study was conducted to evaluatethe growth performance ofnon-descriptCountry chicken under intensive system of management in the poultry unit of the institute. A total of 150 day-old chicks were procured from hatchery unit to study growth parameters. The average bodyweight at 11 weeks was816.04 ± 41.31g. The peak weight gain of 103.76 g was at 8 weeks.The cumulative FCR recorded was 3.26.The cumulative mortality was 3.32 %. The total cost of production/bird up to 11 weeks of age was Rs.158.66 with the returns per bird of 1.18.